Developing senior hospital managers: does 'one size fit all'? - evidence from the evolving Chinese health system - Zhanming Liang; Peter Howard; Jian Wang; Min Xu; Mei Zhao (BMC, 2020)
Abstract Background To improve the effectiveness and efficiency of health service provision in China, the National Health Commission has emphasised that training of all health service managers is essential. However, the implementation of that policy has proven challenging for various reasons, one of which is the lack of understanding of the competency requirements and gaps. The aims of the study were to develop an understanding of the characteristics and training experience of hospital managers in one major Chinese city, explore the difficulties they experience and relate them to their perceived importance of management competencies and the perceived level of their management competency. Methods A cross-sectional, descriptive study with a three-component survey including the use of a validated management competency assessment tool was conducted with three senior executive groups (n = 498) from three categories of hospital in Jinan, Shandong Province, China. Results The survey confirmed that formal and informal management training amongst participants before commencing their management positions was inadequate. The core competencies identified in the Australia context were applicable to the management roles in Chinese hospitals. In addition, the senior executives had low levels of confidence in their management competence. Furthermore, the data showed significant differences between hospital categories and management levels in terms of their commitment to formal and informal training and self-perceived management competence. Conclusions The study suggests that management training and support should be provided using a systematic approach with specific consideration to hospital types and management levels and positions. Such an approach should include clear competency requirements to guide management position recruitment and performance management.